Impact of psychological capital on job satisfaction: moderating role of perceived organizational support and emotional intelligence - Yao, Guannan; Dato’mansor, Zuraina; Ghazali, Hazrina; Yan, Zhen (Arts and Science Press, 2024)
Researchers in today's corporate world are particularly interested in the positive psychology and social exchange interaction. When an individual's emotional intelligence is strong, they exhibit traits like optimism, hope, resilience, and self-efficacy, which are together known as psychological capital (PsyCap). Interactions between organisations and their workers, characterised by rules of reciprocity and social exchanges, have a direct impact on the level of dedication shown by employees. How much care and value an organization's workers feel is reflected in their perceived organizational support (POS). Therefore, the purpose of this study was to examine the effect of psychological capital (PsyCap) on job satisfaction through moderating role of and emotional intelligence (EI). Data was collected from cross border e-commerce industry employees operating in China. A total of 483 responses were obtained from technology staff, and senior managers. Data were used for analysis using PLS-SEM (Smart PLS 4) to test hypothesis relationships. Study hypotheses were accepted and finding shows a positive relationship between the variables. Similarly, understanding the association between PsyCap and job satisfaction is crucial for businesses and their workforces. Result revealed perceived organizational support and emotional intelligence both have positive and significant moderating influence on the relationship between PsyCap and job satisfaction. Therefore, current study suggested that employees are able to provide high motivation because they have a high level of PsyCap and job satisfaction. In this way, they are more likely to put in significant effort on behalf of the company. PsyCap is an untapped positive resource that can improve employees’ job satisfaction and performance, boosting global competitiveness.